Evaluation of anthracycline-induced subclinical LV dysfunction by using myocardial composite index and two-dimension speckle tracking echocardiography technique - Jiabao Zhu; Shuhui Xie; Hanzhen Ji; Xingxing Gu; Jing Wu (Frontiers in Cardiovascular Medicine, 2022)
ObjectiveTo obtain various myocardial strain parameters by using two-dimension speckle tracking echocardiography (2D-STE) technique, calculate the myocardial composite index (MCI) which combines the global longitudinal strain (GLS) of left ventricle and the left ventricular twist (LVtw), and evaluate their diagnostic efficacies for subclinical left ventricular (LV) dysfunction in patients undergoing anthracycline chemotherapy.MethodsA total of 35 female breast cancer patients, who underwent postoperative chemotherapy in the Department of Thyroid and Breast Surgery of Nantong Third People’s Hospital from September 2018 to December 2019 and had successful follow-up, were included into the chemotherapy group, and the patients were evaluated respectively at baseline and in early, interim and later chemotherapy stages according to the course of chemotherapy; in addition, 30 healthy women undergoing physical examination during the same period were included into the control group. In different chemotherapy stages, the data such as left ventricular end diastolic diameter (LVEDD), left ventricular end systolic diameter (LVESD), interventricular septal thickness (IVST), left ventricular posterior wall thickness (LVPWT) and left ventricular ejection fraction (LVEF) were collected by using conventional echocardiography, and various myocardial strain parameters such as GLS, global radial strain (GRS), global circumferential strain(GCS) and LVtw were measured using 2D-STE, and then MCI was calculated. Receiver operating characteristic (ROC) curve analysis was performed to evaluate the application values of various parameters in the diagnosis of early cardiotoxicity.ResultsThere was a difference in MCI between patients at baseline and in the early chemotherapy stage; there were differences in GLS, LVtw and MCI between patients at baseline and in the interim chemotherapy stage; there were differences in four parameters such as MCI, GLS, LVtw and GCS between patients at baseline and in the later chemotherapy stage; The AUC of MCI was 0.915, when the cutoff value was –210.89 (%×°), the sensitivity and specificity were 84.37% and 90.41%, respectively.ConclusionMCI combines the longitudinal and torsional motions of myocardium, and thus has a better diagnostic value for early detection of subclinical LV dysfunction caused by anthracycline chemotherapy drugs compared with strain parameters in a single direction.